Pulmonary tuberculosis mimicking a lung mass - Agarwal, Abhishek; Sharma, Rachit; Verma, Ashish; Verma, Anand (International Journal of Advances in Medicine, 2017)
Pulmonary tuberculosis is commonly seen in India. The usual presentation of the disease is in the form of consolidation involving the upper lobe or the superior segment of the lower lobe. But sometimes the disease has an atypical presentation. Here, we are describing a case report in which the pulmonary tuberculosis presented radiologically as a lung mass and the diagnosis was made by fine needle aspiration cytology from the mass like opacity in the right lung.